Free amino acids, biogenic amines, and ammonium profiling in tobacco from different geographical origins using microwave‐assisted extraction followed by ultra high performance liquid chromatography. Issue 23 (13th November 2017) - Cai, Kai; Xiang, Zhangmin; Li, Hongqin; Zhao, Huina; Lin, Yechun; Pan, Wenjie; Lei, Bo
Abstract: This work describes a rapid, stable, and accurate method for determining the free amino acids, biogenic amines, and ammonium in tobacco. The target analytes were extracted with microwave‐assisted extraction and then derivatized with diethyl ethoxymethylenemalonate, followed by ultra high performance liquid chromatography analysis. The experimental design used to optimize the microwave‐assisted extraction conditions showed that the optimal extraction time was 10 min with a temperature of 60°C. The stability of aminoenone derivatives was improved by keeping the pH near 9.0, and there was no obvious degradation during the 80°C heating and room temperature storage. Under optimal conditions, this method showed good linearity ( R 2 > 0.999) and sensitivity (limits of detection 0.010–0.081 μg/mL). The extraction recoveries were between 88.4 and 106.5%, while the repeatability and reproducibility ranged from 0.48 to 5.12% and from 1.56 to 6.52%, respectively. The newly developed method was employed to analyze the tobacco from different geographical origins. Principal component analysis showed that four geographical origins of tobacco could be clearly distinguished and that each had their characteristic components. The proposed method also showed great potential for further investigations on nitrogen metabolism in plants.